Genetic and proteomic analysis of the MHC class I repertoire from four ovine haplotypes - Ballingall, Keith T.; Chai, Zhong-Wei; Mclean, Kevin; Rocchi, Mara; Yaga, Raja; McKeever, Declan J.; Miltiadou, Despoina (My University, 2008)
Immunity to livestock diseases can be studied directly in the target animal, but its elucidation is often constrained by the lack of major histocompatibility complex (MHC)-defined animals. To address this issue, we have established an MHC-defined sheep resource flock generated around four diverse MHC haplotypes. Initial characterisation of the repertoire of transcribed MHC class I genes identified three class I transcripts associated with each haplotype. Nucleotide sequence, transcript abundance and phylogenetic analysis indicated that they represent alleles at up to four polymorphic loci that vary in number between the different haplotypes. The functional significance of each of these genes is evaluated here using complementary molecular genetic and proteomic approaches. We determine which genes give rise to proteins that localise to the surface of transfected cells. In addition, we provide data to support the generation of expressed products, based on immunoprecipitation of class I products from animals homozygous for each of the four MHC haplotypes followed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. This provides a clearer picture of the number of MHC class I loci in sheep and allows more rational prediction of their classical (class Ia) or non-classical (class Ib) nature. On the basis of the cellular localisation, phylogenetic and transcriptional analyses, we propose that the ovine MHC comprises a minimum of eight class I loci, with considerable variation between haplotypes.
Keywords: Ovine; MHC class I; Haplotype; Expression